A self-igniting coal gangue full-light concrete brick and its preparation method and application
By adopting technical means of self-ignited coal gangue fully light concrete bricks, the problems of high production costs, high energy consumption and environmental pollution of Huipai building materials have been solved, and the lightweight, high-strength and environmentally friendly Huipai antique brick production has been achieved, which has enhanced the added value of the product and market competitiveness.
Patent Information
- Application Number
- CN202211270484.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing Huipai building materials have high production costs, high energy consumption, low efficiency and pollute the environment. The use of natural sand and gravel and ceramics brings resource and environmental pressure.
Self-ignited coal gangue is fully light concrete bricks, including cement, fly ash, silica fume, self-ignited coal gangue coarse aggregate, self-ignited coal gangue sand fine aggregate, water reducing agent, early strength agent, gas induction agent, polypropylene mixed fiber and functional materials. Through optimized ratio and process, Huipai antique bricks with lightweight, high strength and environmental protection characteristics are prepared.
The production cost, energy consumption and environmental protection effects of Huipai antique bricks have been reduced, and the resource and environmental problems of traditional building materials have been solved, while improving the added value of products and market competitiveness.
Smart Images

Figure CN116143480B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal gangue utilization, and particularly relates to a self-igniting coal gangue full-light concrete brick and a preparation method and application thereof. Background Art
[0002] Different schools of architecture write their own stories with their unique historical and cultural accumulation. Among them, most of the Hui-style houses are exquisitely carved with blue tiles and white walls, while the Su-style buildings are mainly light and elegant brick-carved gatehouses. The earliest bricks in China appeared between 3500 BC and 3000 BC. They were made of fine red pottery and fired at high temperatures. Blue bricks appeared in the Western Han Dynasty. The color of the brick blank is red (high-priced iron oxide) when fired in an oxidizing atmosphere. If the brick blank is fired in a reducing atmosphere through processes such as water spraying and kiln suffocation, the high-priced iron oxide is reduced to ferrous oxide, and the product appears blue. Blue bricks are denser in texture, wear-resistant, corrosion-resistant, and more durable than red bricks. However, it is difficult to create a reducing atmosphere with modern production processes. Therefore, most of the sintered bricks we see now are red, and blue bricks are often produced in small workshops, and the product quality fluctuates greatly. In addition, sintered products consume energy and pollute the environment, which can no longer meet the development needs of building industrialization. With the development of society and the advancement of science and technology, traditional building materials and construction methods are gradually replaced by new materials and new construction methods. The self-igniting coal gangue full-light concrete antique brick proposed in the present invention can be said to be a new type of Hui style building material that has emerged with the development of society.
[0003] In addition, with the rise of modern tourism, the unique artistic characteristics and historical value of Huizhou architecture have been discovered. And with the improvement of people's living standards, the special decorative effect of antique bricks returning to nature and simplicity caters to the taste of modern urban people. Many tourist attractions and ordinary residents have begun to use antique bricks for indoor and outdoor decoration, gradually forming a landscape. However, at present, most floor tile manufacturers in my country generally use natural sand and stone to make concrete antique bricks, and use ceramsite to prepare lightweight concrete antique wall tiles. With the continuous increase in resource and environmental constraints, natural sand and stone aggregates and clay sintered ceramsite put companies under great economic and environmental pressure. Self-ignited coal gangue fully lightweight concrete antique bricks can completely solve the above bottleneck problems. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a self-combustion coal gangue full light concrete brick and its preparation method and application in view of the above-mentioned deficiencies of the prior art. The apparent density of the self-combustion coal gangue full light concrete brick of the present invention is 1920kg / m 3 ~2100kg / m 3 , which can be used to prepare Anhui style antique bricks, solves the problems of high production cost, high energy consumption, low efficiency and environmental pollution of traditional Anhui style building materials, and provides a new green development direction for the production of antique bricks.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a self-igniting coal gangue full light concrete brick, comprising the following raw materials by weight: 1 part of cement, 0 to 0.25 parts of fly ash, 0 to 0.006 parts of silica fume, 1.1 to 2.0 parts of self-igniting coal gangue coarse aggregate, 0.35 to 2.1 parts of self-igniting coal gangue sand fine aggregate, 0.4 to 0.5 parts of mixing water, 0.02 to 0.031 parts of water reducer, 0 to 0.03 parts of early strength agent, 0 to 0.0008 parts of air entraining agent, 0 to 0.005 parts of polypropylene mixed fiber and 0 to 0.111 parts of functional material; the cement is R·SAC42.5 sulphoaluminate cement or P·O42.5 ordinary Portland cement; the spontaneous combustion gangue coarse aggregate and spontaneous combustion gangue sand fine aggregate are both mixtures of spontaneous combustion gangue and spontaneous combustion gangue ceramsite; the water reducer is polycarboxylic acid water reducer or naphthalene water reducer; the functional material is a mixture of latex powder, defoamer and brightener or a mixture of latex powder, defoamer, brightener and pigment.
[0006] Preferably, the spontaneous combustion coal gangue coarse aggregate is a continuous particle size of nominal particle size d 1 , 5mm<d 1 ≤20mm; the self-igniting coal gangue fine aggregate is a nominal particle size d of continuous particle size 2 ≤5mm.
[0007] Preferably, the polypropylene mixed fiber is a mixture of polypropylene coarse fiber and polypropylene fine fiber in a mass ratio of 4:1; the length of the polypropylene coarse fiber is 40 mm and the diameter is 2 mm, and the length of the polypropylene fine fiber is 20 mm and the diameter is 0.5 mm.
[0008] Preferably, the water reducer is JJ-A type ether polycarboxylate water reducer or FDN-C type naphthalene series water reducer; the air entraining agent is a modified rosin thermal polymer air entraining agent; and the early strength agent is a FCM-10 type nano early strength agent.
[0009] Preferably, the latex powder is VAE renewable dispersed latex powder, the defoamer is SJ-101 defoamer, the brightener is CP3005 brightener, and the pigment is a metal oxide pigment.
[0010] Self-combustion coal gangue fully lightweight concrete bricks contain self-combustion coal gangue coarse aggregate and self-combustion coal gangue sand fine aggregate, which account for 68% to 80% of the total mass of concrete. The product is energy-saving and environmentally friendly. Self-combustion coal gangue has a large porosity and high water absorption rate. The aggregate has a "micro-pump" effect and has a certain activity, which can improve the structure of the interface transition zone between the aggregate and the cement matrix. The matching degree between the three phases of self-combustion coal gangue aggregate, cement stone and interface transition zone is high, so self-combustion coal gangue can be used to prepare medium-strength grade concrete bricks. On this basis, by adding air entraining agents, reinforcing agents and various functional materials, the durability of self-combustion coal gangue fully lightweight concrete bricks can be guaranteed.
[0011] The present invention also provides a method for preparing the self-igniting coal gangue fully light concrete brick, which comprises:
[0012] S1. Raw material pretreatment:
[0013] The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then mixed evenly to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour;
[0014] Mix cement, fly ash and silica fume uniformly to obtain a mixture b;
[0015] Mixing the functional materials uniformly to obtain a mixture c;
[0016] The water reducing agent, early strength agent and air entraining agent are mixed and added into the mixing water and stirred evenly to obtain a mixture d;
[0017] S2, mixing: Mixture a and mixture b in S1 are mixed evenly, then the polypropylene mixed fiber is added and mixed evenly, then mixture c is added and mixed evenly, and finally mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is ≥10min;
[0018] S3, pouring and vibrating: pouring the concrete mixture obtained in S2 into a silica gel mold, vibrating and molding, and obtaining a semi-finished self-combustion coal gangue fully light concrete brick; when the cement is R·SAC42.5 sulphoaluminate cement, covering and sprinkling water are carried out within 30 minutes after pouring;
[0019] S4, curing: curing the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 to obtain the self-combustion coal gangue fully light concrete brick;
[0020] When the cement is P·O42.5 ordinary Portland cement, the curing method of the semi-finished self-combustion coal gangue fully light concrete brick is temperature-controlled and humidity-controlled curing, and the method of temperature-controlled and humidity-controlled curing is: the semi-finished self-combustion coal gangue fully light concrete brick is placed in a natural environment and left to stand for 30 minutes, heated to 50°C at a heating rate of 20°C / h, kept at a constant temperature for 4 hours, and then naturally cooled to room temperature and demolded, and then naturally cured; the humidity during the temperature-controlled and humidity-controlled curing process is 60% to 80%; the temperature-controlled and humidity-controlled curing method takes a total of 16h to 20h; the 28d compressive strength of the self-combustion coal gangue fully light concrete brick is 27.7MPa to 31.5MPa;
[0021] When the cement is R·SAC42.5 sulphoaluminate cement, the curing method of the self-combustion coal gangue fully lightweight concrete brick semi-finished product is natural curing; the natural curing method is: placing the self-combustion coal gangue fully lightweight concrete brick semi-finished product in a natural environment for curing for 2h to 4h, then removing the mold and curing it in a natural environment for 3d; the 3d compressive strength of the self-combustion coal gangue fully lightweight concrete brick is 26.8MPa to 27.9MPa.
[0022] Preferably, the apparent density of the self-combustion coal gangue fully lightweight concrete brick in S4 is 1920 kg / m 3 ~2138kg / m 3 .
[0023] Spontaneous combustion coal gangue full light concrete is different from ordinary concrete. Excessive humidity is not conducive to the strength development of spontaneous combustion coal gangue full light concrete, especially the flexural strength of spontaneous combustion coal gangue full light concrete. This is mainly because the pores of spontaneous combustion coal gangue aggregate are large, and most of them are nano-scale open pores. Excessive humidity weakens the strength of spontaneous combustion coal gangue aggregate and reduces the "internal maintenance" effect of spontaneous combustion coal gangue aggregate.
[0024] The present invention also provides an application of the above-mentioned self-igniting coal gangue fully lightweight concrete bricks. The self-igniting coal gangue fully lightweight concrete bricks can be used for building Hui style antique bricks. They are different from the existing ordinary concrete bricks and sintered bricks on the market. They have the characteristics of light weight, high strength, environmental protection, simple production process and low energy consumption. They can be used as enclosure materials, load-bearing materials and detail decorative materials. The products can organically combine the beauty of Hui style materials and the beauty of spatial structure.
[0025] The self-igniting coal gangue full-light concrete brick prepared by the present invention has a strength grade of ≥C20 and a frost resistance grade of ≥F50.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] The self-combustion coal gangue fully lightweight concrete brick prepared by the present invention has a strength grade of ≥C20, a frost resistance grade of ≥F50, and an apparent density of 1920kg / m3 ~2138kg / m 3 Different from the existing ordinary concrete bricks and sintered bricks on the market, the present invention has the characteristics of light weight, high strength, environmental protection, simple production process and low energy consumption. It can be used as both enclosure material and load-bearing material. With the help of silicone molds, it can also be used as detail decorative material. The product can organically combine the beauty of Hui style materials and the beauty of spatial structure. The prepared Hui style antique bricks can be used in Hui style buildings, solving the problems of high production cost, high energy consumption, low efficiency and environmental pollution of traditional Hui style building materials. It also makes full use of spontaneous combustion coal gangue solid waste, complies with my country's policy of energy conservation and emission reduction, and the products obtained have high added value and obvious price advantages, providing a new green development direction for the production of antique bricks.
[0028] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The self-igniting coal gangue full-light concrete brick in Example 1 of the present invention is used as an antique wall brick in the Anhui style antique brick for construction.
[0030] Figure 2 This is an application effect diagram of the self-igniting coal gangue full-light concrete bricks in Example 5 of the present invention used for wall and floor tiles of Hui style antique bricks for construction. DETAILED DESCRIPTION
[0031] Example 1
[0032] The self-igniting coal gangue fully lightweight concrete brick of this embodiment includes the following raw materials in parts by weight: 1 part of R·SAC42.5 sulphoaluminate cement, 1.1 parts of self-igniting coal gangue coarse aggregate, 0.35 parts of self-igniting coal gangue sand fine aggregate, 0.4 parts of mixing water, 0.02 parts of JJ-A type ether polycarboxylate water reducer, 0.003 parts of polypropylene mixed fiber and 0.111 parts of functional materials; the JJ-A concrete pumping type water reducer is an ester type polycarboxylate water reducer; the functional materials include 0.006 parts of VAE renewable disperse latex powder, 0.001 parts of SJ-101 type defoamer, 0.004 parts of CP3005 type brightener and 0.1 parts of iron ash pigment;
[0033] Self-combustion coal gangue fully lightweight concrete bricks contain self-combustion coal gangue coarse aggregate and self-combustion coal gangue sand fine aggregate, and the product is energy-saving and environmentally friendly. Self-combustion coal gangue has large porosity and high water absorption rate. The aggregate has a "micro-pump" effect and has a certain activity, which can improve the structure of the interface transition zone between aggregate and cement matrix. The matching degree between the three phases of self-combustion coal gangue aggregate, cement stone and interface transition zone is high, so self-combustion coal gangue can be used to prepare medium-strength grade concrete bricks. On this basis, by adding air entraining agents, reinforcing agents and various functional materials, the durability of self-combustion coal gangue fully lightweight concrete bricks such as frost resistance can be guaranteed.
[0034] The self-igniting coal gangue coarse aggregate and the self-igniting coal gangue sand fine aggregate are both a mixture of self-igniting coal gangue and self-igniting coal gangue ceramsite; the self-igniting coal gangue coarse aggregate is a continuous particle size of nominal particle size d 1 , 5mm<d 1 ≤15mm, grade matching format; the self-igniting coal gangue fine aggregate is a nominal particle size d of continuous particle size 2 ≤5mm, grade matching qualification.
[0035] The polypropylene mixed fiber is a mixture of polypropylene coarse fiber and polypropylene fine fiber in a mass ratio of 4:1; the length of the polypropylene coarse fiber is 40 mm and the diameter is 2 mm, and the length of the polypropylene fine fiber is 20 mm and the diameter is 0.5 mm.
[0036] This embodiment also provides a method for preparing the above-mentioned self-igniting coal gangue full-light concrete brick, which is:
[0037] S1. Raw material pretreatment:
[0038] The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then mixed evenly to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour;
[0039] Mixing R·SAC42.5 sulphoaluminate cement uniformly to obtain mixture b;
[0040] Mixing VAE renewable dispersed latex powder, SJ-101 defoamer, CP3005 brightener and metal oxide pigment to obtain mixture c;
[0041] Add JJ-A type ether polycarboxylate water reducer into mixing water and stir evenly to obtain mixture d;
[0042] S2, mixing: Mixture a and mixture b in S1 are mixed evenly, then the polypropylene mixed fiber is added and mixed evenly, then mixture c is added and mixed evenly, and finally mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is 13 minutes;
[0043] S3, pouring and vibrating: pouring the concrete mixture obtained in S2 into a silica gel mold, vibrating and molding, and obtaining a semi-finished self-combustion coal gangue fully light concrete brick, which is covered and sprinkled with water within 20 minutes after pouring;
[0044] S4, curing: performing natural curing on the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 to obtain the self-combustion coal gangue fully light concrete brick;
[0045] The natural curing method is: curing the self-igniting coal gangue fully lightweight concrete brick semi-finished product in a natural environment for 2 hours, removing the mold, and then curing it in a natural environment for 3 days.
[0046] Sprinkling water during natural curing and spraying water to maintain humidity during temperature and humidity control are both curing water. At this time, the concrete has hardened and the curing water only plays a moisturizing role. In addition, according to the preparation requirements of lightweight aggregate concrete, in order to ensure that the workability of the concrete mixture meets the construction requirements, additional water must be added 1 hour in advance. In this embodiment, the coarse aggregate of spontaneous combustion coal gangue is added with additional water at a water absorption rate of 80% in 1 hour, and the fine aggregate of spontaneous combustion coal gangue is added with additional water at a water absorption rate of 60% in 1 hour. The workability of the obtained concrete mixture meets the requirements.
[0047] According to the "Standard for Test Methods of Ordinary Concrete Mixture Performance" (GB / T50080-2002) and the "Standard for Test Methods of Ordinary Concrete Mechanical Properties" (GB / T50081-2016), the apparent density and compressive strength of the self-igniting coal gangue full-light concrete cube specimen formed in this embodiment were tested. The specimen size was 100×100×100mm. The measured apparent density value was 1920kg / m 3 The 1d compressive and splitting tensile strengths were 19.2MPa and 1.92MPa respectively, the 3d compressive and splitting tensile strengths were 26.9MPa and 2.07MPa respectively, and the 14d compressive and splitting tensile strengths were 27.3MPa and 2.21MPa respectively.
[0048] The cement used in the self-igniting coal gangue fully lightweight concrete bricks prepared in this embodiment is sulphoaluminate cement. According to national standards, the strength grade is determined by the 3d compressive strength. Therefore, the 3d strength of the self-igniting coal gangue fully lightweight concrete bricks prepared in this embodiment meets the design requirements of the C20 concrete strength grade.
[0049] The appearance of the self-combustion coal gangue full light concrete brick prepared in this example is detailed in Figure 1 .from Figure 1It can be clearly seen that the surface of the product is smooth and full, the product shape is clear and has a strong retro color. This is because the slurry-solid ratio in the mix ratio of this embodiment is as high as 0.68, and secondly, it is because silicone molds are used for molding. Silicone molds have the characteristics of environmental protection, high temperature resistance, corrosion resistance, strong tear resistance and high simulation fineness. The self-igniting coal gangue fully lightweight concrete bricks prepared in this embodiment are different from the existing ordinary concrete bricks and sintered bricks on the market. They have the characteristics of light weight, high strength, environmental protection, simple production process and low energy consumption. They can be used as enclosure materials, load-bearing materials and detail decoration materials. The product can organically combine the beauty of Hui style materials and the beauty of spatial structure, solving the problems of high production cost, high energy consumption, low efficiency and environmental pollution of traditional Hui style building materials, and providing a new green development direction for the production of antique bricks.
[0050] Example 2
[0051] The self-igniting coal gangue fully lightweight concrete brick of this embodiment includes the following raw materials in parts by weight: 1 part of R·SAC42.5 sulphoaluminate cement, 1.4 parts of self-igniting coal gangue coarse aggregate, 1.7 parts of self-igniting coal gangue sand fine aggregate, 0.4 parts of mixing water, 0.02 parts of JJ-A type ether polycarboxylate water reducer, 0.004 parts of polypropylene mixed fiber and 0.002 parts of functional materials; the mass ratio of VAE renewable disperse latex powder, SJ-101 type defoamer and CP3005 type brightener in the functional materials is 6:1:4;
[0052] The self-igniting coal gangue coarse aggregate and the self-igniting coal gangue sand fine aggregate are both a mixture of self-igniting coal gangue and self-igniting coal gangue ceramsite; the self-igniting coal gangue coarse aggregate is a continuous particle size of nominal particle size d 1 , 5mm<d 1 ≤20mm, grade matching format; the self-igniting coal gangue fine aggregate is a nominal particle size d of continuous particle size 2 ≤5mm, grade matching qualification.
[0053] The polypropylene mixed fiber is a mixture of polypropylene coarse fiber and polypropylene fine fiber in a mass ratio of 4:1; the length of the polypropylene coarse fiber is 40 mm and the diameter is 2 mm, and the length of the polypropylene fine fiber is 20 mm and the diameter is 0.5 mm.
[0054] This embodiment also provides a method for preparing the above-mentioned self-igniting coal gangue full-light concrete brick, which is:
[0055] S1. Raw material pretreatment:
[0056] The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then mixed evenly to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour;
[0057] Mixing R·SAC42.5 sulphoaluminate cement uniformly to obtain mixture b;
[0058] VAE renewable dispersed latex powder, SJ-101 defoamer and CP3005 brightener were mixed uniformly in a mass ratio of 6:1:4 to obtain a mixture c;
[0059] Add JJ-A concrete pumpable water reducer into the mixing water and stir evenly to obtain mixture d;
[0060] S2, mixing: Mixture a and mixture b in S1 are mixed evenly, then the polypropylene mixed fiber is added and mixed evenly, then mixture c is added and mixed evenly, and finally mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is 12 minutes;
[0061] S3, pouring and vibrating: pouring the concrete mixture obtained in S2 into a silica gel mold, vibrating and molding, and obtaining a semi-finished self-combustion coal gangue fully light concrete brick, which is covered and sprinkled with water within 25 minutes after pouring;
[0062] S4, curing: performing natural curing on the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 to obtain the self-combustion coal gangue fully light concrete brick;
[0063] The natural curing method is: placing the self-igniting coal gangue fully lightweight concrete brick semi-finished product in a natural environment for curing for 2 hours, then removing the mold, and continuing to place it in a natural environment for curing for 3 days.
[0064] According to the Standard for Experimental Methods of Mechanical Properties of Ordinary Concrete (GB / T50081-2016), the compressive strength of the self-igniting coal gangue light concrete cube specimen prepared in this embodiment was tested, and the specimen size was a cube specimen of 100×100×100mm. The 1d compressive strength was 19.2MPa, the 3d compressive strength was 27.9MPa, and the 14d compressive strength was 31.5MPa.
[0065] The cement used in the self-combustion coal gangue light concrete bricks prepared in this embodiment is sulphoaluminate cement. According to the national standard, the strength grade is determined by the 3d compressive strength. Therefore, the 3d strength of the self-combustion coal gangue light concrete bricks prepared in this embodiment meets the design requirements of the C20 concrete strength grade. It can be seen from the mix ratio of the embodiment that the slurry-solid ratio is only 0.32, the coarse aggregate of self-combustion coal gangue and the fine aggregate of self-combustion coal gangue account for 80% of the total mass of concrete, the amount of cementitious material is small, and the amount of solid waste aggregate is large, so the product has an obvious price advantage.
[0066] Example 3
[0067] The self-combustion coal gangue full light concrete brick of this embodiment includes the following raw materials by weight: 1 part of P·O42.5 ordinary Portland cement, 0.1 part of fly ash, 1.6 parts of self-combustion coal gangue coarse aggregate, 1.9 parts of self-combustion coal gangue sand fine aggregate, 0.4 parts of mixing water, 0.028 parts of FDN-C naphthalene water reducer, 0.01 parts of FCM-10 nano early strength agent, and 0.0045 parts of polypropylene mixed fiber;
[0068] The self-igniting coal gangue coarse aggregate and the self-igniting coal gangue sand fine aggregate are both a mixture of self-igniting coal gangue and self-igniting coal gangue ceramsite; the self-igniting coal gangue coarse aggregate is a continuous particle size of nominal particle size d 1 , 5mm<d 1 ≤20mm, grade matching format; the self-igniting coal gangue fine aggregate is a nominal particle size d of continuous particle size 2 ≤5mm, grade matching qualification.
[0069] The polypropylene mixed fiber is a mixture of polypropylene coarse fiber and polypropylene fine fiber in a mass ratio of 4:1; the length of the polypropylene coarse fiber is 40 mm and the diameter is 2 mm, and the length of the polypropylene fine fiber is 20 mm and the diameter is 0.5 mm.
[0070] This embodiment also provides a method for preparing the above-mentioned self-igniting coal gangue full-light concrete brick, which is:
[0071] S1. Raw material pretreatment:
[0072] The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then uniformly mixed to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour;
[0073] P·O42.5 ordinary Portland cement and fly ash are uniformly mixed to obtain mixture b;
[0074] Mix FDN-C naphthalene water reducing agent and FCM-10 nano early strength agent, add them into mixing water and stir evenly to obtain mixture d;
[0075] S2, mixing: Mixture a and mixture b in S1 are mixed evenly; then polypropylene mixed fiber is added and mixed evenly; finally, mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is 10 minutes;
[0076] S3, pouring and vibrating to form: pouring the concrete mixture obtained in S2 into a silica gel mold, vibrating and forming, and obtaining a semi-finished self-igniting coal gangue fully lightweight concrete brick;
[0077] S4, curing: curing the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 by controlling temperature and humidity to obtain the self-combustion coal gangue fully light concrete brick;
[0078] The temperature and humidity control curing method is as follows: the semi-finished self-igniting coal gangue fully lightweight concrete brick is placed in a natural environment and left there for 30 minutes, heated to 50°C at a heating rate of 20°C / h, and kept at a constant temperature for 4 hours, and then naturally cooled to room temperature and demolded, followed by natural curing; the humidity during the temperature and humidity control curing process is 60%; the temperature and humidity control curing method takes a total of 20 hours.
[0079] Spontaneous combustion coal gangue full light concrete is different from ordinary concrete. Excessive humidity is not conducive to the strength development of spontaneous combustion coal gangue full light concrete, especially the flexural strength of spontaneous combustion coal gangue full light concrete. This is mainly because the pores of spontaneous combustion coal gangue aggregate are large, and most of them are nano-scale open pores. Excessive humidity weakens the strength of spontaneous combustion coal gangue aggregate and reduces the "internal maintenance" effect of spontaneous combustion coal gangue aggregate.
[0080] According to the "Standard for Test Methods of Ordinary Concrete Mixture Performance" (GB / T50080-2002) and the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2016), the apparent density and compressive strength of the self-ignited coal gangue fully lightweight concrete cube specimen prepared in this embodiment are tested. The specimen size is a 100×100×100mm cube specimen. The apparent density of the self-ignited coal gangue fully lightweight concrete brick prepared in this embodiment is 2138kg / m 3 The 1d compressive strength is 9.3MPa, the 7d compressive strength is 25.7MPa, and the 28d compressive strength is 31.5MPa.
[0081] The self-igniting coal gangue fully lightweight concrete bricks prepared in this embodiment have a 28d compressive strength that meets the design requirements of C20 concrete strength grade.
[0082] In this embodiment, not only ordinary Portland cement is used as cement, but also fly ash replaces 10% of cement, and the coarse and fine aggregates of spontaneous combustion coal gangue account for 70% of the total mass of concrete. Therefore, the spontaneous combustion coal gangue fully lightweight concrete bricks prepared in this embodiment have greater price advantages.
[0083] Example 4
[0084] The self-combustion coal gangue full light concrete brick of this embodiment includes the following raw materials by weight: 1 part of P·O42.5 ordinary Portland cement, 0.25 parts of fly ash, 1.77 parts of self-combustion coal gangue coarse aggregate, 2.1 parts of self-combustion coal gangue sand fine aggregate, 0.5 parts of mixing water, 0.03 parts of FCM-10 type nano early strength agent, 0.031 parts of FDN-C type naphthalene water reducer, and 0.005 parts of polypropylene mixed fiber;
[0085] The self-igniting coal gangue coarse aggregate and the self-igniting coal gangue sand fine aggregate are both a mixture of self-igniting coal gangue and self-igniting coal gangue ceramsite; the self-igniting coal gangue coarse aggregate is a continuous particle size of nominal particle size d 1 , 5mm<d 1 ≤20mm, grade matching format; the self-igniting coal gangue fine aggregate is a nominal particle size d of continuous particle size 2 ≤5mm, grade matching qualification.
[0086] The polypropylene mixed fiber is a mixture of polypropylene coarse fiber and polypropylene fine fiber in a mass ratio of 4:1; the length of the polypropylene coarse fiber is 40 mm and the diameter is 2 mm, and the length of the polypropylene fine fiber is 20 mm and the diameter is 0.5 mm.
[0087] This embodiment also provides a method for preparing the above-mentioned self-igniting coal gangue full-light concrete brick, which is:
[0088] S1. Raw material pretreatment:
[0089] The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then mixed evenly to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour;
[0090] P·O42.5 ordinary Portland cement and fly ash are uniformly mixed to obtain mixture b;
[0091] Mix FDN-C naphthalene water reducing agent and FCM-10 nano early strength agent, add them into mixing water and stir evenly to obtain mixture d;
[0092] S2, mixing: Mixture a and mixture b in S1 are mixed evenly; then polypropylene mixed fiber is added and mixed evenly; finally, mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is 12 minutes;
[0093] S3, pouring and vibrating to form: pouring the concrete mixture obtained in S2 into a silica gel mold, vibrating and forming, and obtaining a semi-finished self-igniting coal gangue fully lightweight concrete brick;
[0094] S4, curing: curing the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 by controlling temperature and humidity to obtain the self-combustion coal gangue fully light concrete brick;
[0095] The temperature and humidity control curing method is as follows: the semi-finished self-igniting coal gangue fully lightweight concrete brick is placed in a natural environment for 30 minutes, heated to 50°C at a heating rate of 20°C / h, and kept at a constant temperature for 4 hours, then naturally cooled to room temperature and demolded, and then naturally cured; the humidity during the temperature and humidity control curing process is 80%; the temperature and humidity control curing method takes a total of 16 hours.
[0096] According to the "Standard for Test Methods of Ordinary Concrete Mixture Performance" (GB / T50080-2002) and the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2016), the apparent density and compressive strength of the self-ignited coal gangue fully lightweight concrete cube specimen prepared in this embodiment are tested. The specimen size is a cubic specimen of 100×100×100mm. The apparent density of the self-ignited coal gangue fully lightweight concrete brick prepared in this embodiment is 2102kg / m 3 The 1d compressive strength is 8.6MPa, the 7d compressive strength is 24.4MPa, and the 28d compressive strength is 27.7MPa.
[0097] The self-igniting coal gangue fully lightweight concrete bricks prepared in this embodiment have a 28d compressive strength that meets the design requirements of C20 concrete strength grade.
[0098] In this embodiment, not only ordinary Portland cement is selected as the cement, but also the ratio of fly ash as an auxiliary cementitious material to cement is increased from 1:10 in Example 3 to 2:8. In addition, the coarse and fine aggregates of self-ignited coal gangue account for 68% of the total mass of concrete. Therefore, the self-ignited coal gangue fully lightweight concrete bricks prepared in this embodiment have a greater price advantage than those in Example 3.
[0099] It can be seen from Examples 1 to 4 that the strength of the self-igniting coal gangue full light concrete bricks prepared with two different cements, R·SAC42.5 sulphoaluminate cement and R·SAC42.5 sulphoaluminate cement, can reach the design requirements of C20 strength grade. When R·SAC42.5 sulphoaluminate cement is used, the product production cycle is short and the mold turnover rate is high, but the price of sulphoaluminate cement is relatively high; when P·O42.5 grade ordinary Portland cement is used, the product needs steam curing, and the production cost is increased, but the price of Portland cement is only half of that of sulphoaluminate cement, so the products of Examples 3 and 4 have greater market competitiveness.
[0100] Example 5
[0101] The self-igniting coal gangue full light concrete brick of this embodiment includes the following raw materials by weight: 1 part of R·SAC42.5 sulphoaluminate cement, 0.25 parts of fly ash, 0.006 parts of silica fume, 2.0 parts of self-igniting coal gangue coarse aggregate, 1.7 parts of self-igniting coal gangue sand fine aggregate, 0.43 parts of mixing water, 0.025 parts of JJ-A type ether polycarboxylic acid water reducer, and 0.0008 parts of modified rosin thermal polymer air entraining agent; the bulk density of the silica fume is 283kg / m 3 .
[0102] The self-igniting coal gangue coarse aggregate and the self-igniting coal gangue sand fine aggregate are both a mixture of self-igniting coal gangue and self-igniting coal gangue ceramsite; the self-igniting coal gangue coarse aggregate is a continuous particle size of nominal particle size d 1 , 5mm<d 1 ≤15mm, grade matching format; the self-igniting coal gangue fine aggregate is a nominal particle size d of continuous particle size 2 ≤5mm, grade matching qualification.
[0103] This embodiment also provides a method for preparing the above-mentioned self-igniting coal gangue full-light concrete brick, which is:
[0104] S1. Raw material pretreatment:
[0105] The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then mixed evenly to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour;
[0106] R·SAC42.5 sulphoaluminate cement, fly ash and silica fume are uniformly mixed to obtain a mixture b;
[0107] Mix JJ-A type ether polycarboxylate water reducer and modified rosin thermal polymer air entraining agent, add them into mixing water and stir evenly to obtain mixture d;
[0108] S2, mixing: Mixture a and mixture b in S1 are mixed evenly; then mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is 10 minutes;
[0109] S3, pouring and vibrating: the concrete mixture obtained in S2 is poured into a silica gel mold, vibrated and molded to obtain a semi-finished self-combustion coal gangue fully light concrete brick, which is covered and sprinkled with water within 30 minutes after pouring;
[0110] S4, curing: performing natural curing on the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 to obtain the self-combustion coal gangue fully light concrete brick;
[0111] The natural curing method is: curing the self-igniting coal gangue fully lightweight concrete brick semi-finished product in a natural environment for 4 hours, removing the mold, and then curing it in a natural environment for 3 days.
[0112] According to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2016) and
[0113] The "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) tests the compressive strength and frost resistance of concrete specimens. The size of the compressive test specimen is 100
[0114] The size of the frost resistance test specimen is a cubic specimen of 100×100mm and the size of the frost resistance test specimen is a prismatic specimen of 100×100×400mm.
[0115] In the frost resistance test, after reaching the age specified in the specification, the initial dynamic elastic modulus and mass of the test piece are first tested, and the relative dynamic elastic modulus and mass loss are tested after 25 freeze-thaw cycles. When the relative dynamic elastic modulus of the test piece drops to 60% or the mass loss reaches 5%, the test is stopped and the number of frost resistance cycles of the test piece is recorded. The test results of this embodiment are shown in Table 1:
[0116] Table 1 Compression and frost resistance test results of self-igniting coal gangue full light concrete bricks in Example 5
[0117]
[0118] It can be seen from Table 1 above that after 25 freeze-thaw cycles, the dynamic elastic modulus loss rate of the self-combustion coal gangue full-light concrete brick is 6.7%, and the mass loss rate is 1.7%; after 50 freeze-thaw cycles, the dynamic elastic modulus loss rate is 14.2%, and the mass loss rate is 4.83%, indicating that the self-combustion coal gangue full-light concrete brick meets the F50 frost resistance grade requirements, and at the same time, also meets the C20 concrete strength grade requirements.
[0119] It can be seen from this embodiment that the self-combustion coal gangue fully light concrete brick, under the joint action of the composite cementitious materials fly ash and silica fume, the active mineral admixtures absorb water and continue to hydrate, so that the concrete structure is strengthened, and the frost resistance is improved; the addition of air entraining agent introduces a large number of tiny closed bubbles into the concrete, which block and block the capillary channels in the concrete. At the same time, the addition of air entraining agent improves the water retention and reduces the porosity of the concrete caused by sedimentation and bleeding. In addition, because the workability of the concrete is improved, the porosity of the construction is also reduced, so this embodiment meets the design requirements of the F50 frost resistance grade. For the self-combustion coal gangue fully light concrete antique bricks used in outdoor projects in the north, it is recommended to choose the mix ratio of this embodiment.
[0120] For details of the engineering application example of embodiment 5, see Figure 2 shown.
[0121] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a self-combustion coal gangue full-light concrete brick of Hui style antique brick for construction, characterized in that: The self-combustion coal gangue full light concrete brick comprises the following raw materials in parts by weight: 1 part of cement, 0.1 to 0.25 parts of fly ash, 0.006 parts of silica fume, 1.1 to 2.0 parts of self-combustion coal gangue coarse aggregate, 0.35 to 2.1 parts of self-combustion coal gangue sand fine aggregate, 0.4 to 0.5 parts of mixing water, 0.02 to 0.031 parts of water reducer, 0.01 to 0.03 parts of early strength agent, 0.0008 parts of air entraining agent, 0.003 to 0.005 parts of polypropylene mixed fiber and 0.002 to 0.111 parts of functional material; the cement is R.S. AC42.5 sulphoaluminate cement or P·O42.5 ordinary Portland cement; the self-igniting coal gangue coarse aggregate and the self-igniting coal gangue sand fine aggregate are both a mixture of self-igniting coal gangue and self-igniting coal gangue ceramsite; the water reducer is a polycarboxylic acid water reducer or a naphthalene water reducer; the functional material is a mixture of latex powder, defoamer and brightener or a mixture of latex powder, defoamer, brightener and pigment; the self-igniting coal gangue coarse aggregate is a continuous particle size d1, 5mm<d1≤20mm; the self-igniting coal gangue sand fine aggregate is a continuous particle size d2≤5mm; The polypropylene mixed fiber is a mixture of polypropylene coarse fiber and polypropylene fine fiber in a mass ratio of 4:1; the length of the polypropylene coarse fiber is 40 mm and the diameter is 2 mm, and the length of the polypropylene fine fiber is 20 mm and the diameter is 0.5 mm; The polycarboxylate water reducer is a JJ-A type ether polycarboxylate water reducer, the naphthalene water reducer is a FDN-C type naphthalene water reducer; the air entraining agent is a modified rosin thermal polymer air entraining agent; the early strength agent is a FCM-10 type nano early strength agent; The latex powder is VAE renewable dispersed latex powder, the defoamer is SJ-101 defoamer, the brightener is CP3005 brightener, and the pigment is a metal oxide pigment; The preparation method is: S1. Raw material pretreatment: The spontaneous combustion gangue coarse aggregate and the spontaneous combustion gangue sand fine aggregate are subjected to additional water wetting treatment 1 hour in advance, and then mixed evenly to obtain a mixture a; the amount of additional water in the spontaneous combustion gangue coarse aggregate is 80% of the water absorption rate of the spontaneous combustion gangue coarse aggregate in 1 hour; the amount of additional water in the spontaneous combustion gangue sand fine aggregate is 60% of the water absorption rate of the spontaneous combustion gangue sand fine aggregate in 1 hour; Mix cement, fly ash and silica fume uniformly to obtain a mixture b; Mixing the functional materials uniformly to obtain a mixture c; The water reducing agent, early strength agent and air entraining agent are mixed and added into the mixing water and stirred evenly to obtain a mixture d; S2, mixing: Mixture a and mixture b in S1 are mixed evenly, then the polypropylene mixed fiber is added and mixed evenly, then mixture c is added and mixed evenly, and finally mixture d is added and mixed evenly to obtain a concrete mixture; the total mixing time of the concrete mixture is ≥10min; S3, pouring and vibrating: pouring the concrete mixture obtained in S2 into a silica gel mold, vibrating and molding, and obtaining a semi-finished self-combustion coal gangue fully light concrete brick; when the cement is R·SAC42.5 sulphoaluminate cement, covering and sprinkling water are carried out within 30 minutes after pouring; S4, curing: curing the semi-finished self-combustion coal gangue fully light concrete brick obtained in S3 to obtain the self-combustion coal gangue fully light concrete brick; When the cement is P·O42.5 ordinary Portland cement, the curing method of the semi-finished self-combustion coal gangue fully light concrete brick is temperature-controlled and humidity-controlled curing, and the method of temperature-controlled and humidity-controlled curing is: the semi-finished self-combustion coal gangue fully light concrete brick is placed in a natural environment and left to stand for 30 minutes, heated to 50°C at a heating rate of 20°C / h, kept at a constant temperature for 4 hours, and then naturally cooled to room temperature and demolded, and then naturally cured; the humidity during the temperature-controlled and humidity-controlled curing process is 60% to 80%; the temperature-controlled and humidity-controlled curing method takes a total of 16h to 20h; the 28d compressive strength of the self-combustion coal gangue fully light concrete brick is 27.7MPa to 31.5MPa; When the cement is R·SAC42.5 sulphoaluminate cement, the curing method of the semi-finished spontaneous combustion coal gangue fully light concrete brick is natural curing; the method of natural curing is: curing the semi-finished spontaneous combustion coal gangue fully light concrete brick in a natural environment for 2h to 4h, then removing the mold and curing it in a natural environment for 3d; the 3d compressive strength of the spontaneous combustion coal gangue fully light concrete brick is 26.8MPa to 27.9MPa; The apparent density of the self-igniting coal gangue fully lightweight concrete brick described in S4 is 1920kg / m 3 ~2138kg / m 3 ; Strength grade ≥C20, frost resistance grade ≥F50.
Citation Information
Patent Citations
Mix proportion design method of C30-C40 spontaneous combustion coal gangue aggregate concrete
CN113192574A